P169 Reaching more people at the end of life through digital communication. (1st October 2013) - McLaughlin, Kimberley; Miller, Daniel
Abstract : End of Life care is arguably both a public health and diagnosis specific concern. Those living and dying from life threatening illness access support and care from formal (e.g. health and social care) and informal (e.g. community, friends and family) networks. The last few years has seen an explosion in social media and new communication technologies in the informal arena. As hospices face the challenge of extending their reach and realigning their existing resources, researching new ways to support patients and their families is key. A 3 year collaborative study between Professor Daniel Miller (Department of Anthropology, University College London) and Kimberley McLaughlin, Director of Supportive Care (Hospice of St Francis) focuses on the hospice, patients and those living in the community. Aims: To understand the impact and future potential of new communication technologies e.g.webcam, social networking sites and smart phones. To gain the widest and deepest understanding of the role of these technologies in all aspects of communication between people in end of life situations, their carers, family and friends. To research issues including privacy, feelings of security and vulnerability, loneliness, boredom, memorialisation and sense of connexion with others. To explore the relationship between any sense of loss of communicative capacity for persons and simultaneously a gain in communicative capacity as a result of new technologies. To understand the use of communication technologies and health care professionals/hospice staff. This research will: Advance the body of knowledge regarding the use of social media in end of life care as well as researching in sensitive areas. Provide guidance in the use of social media in end of life care. Facilitate communication between end of life individuals who remain in their home and with carers, friends and families both during this period and following upon their death.